(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article examines crimes committed by individuals who are legally entrusted with obligations to educate, instruct, and (or) care for the victim, as well as to exercise supervision over the victim, treating such obligations as an optional characteristic of the offender in criminal law. Special emphasis is placed on the heightened social danger of sexual offences committed against minors by employees of educational, medical, and other institutions, the pronounced latent nature of these crimes, and their detrimental impact on the psychological and physical development of victims. Within the scope of the study, the criminal legislation of Germany, France, Spain, and Kazakhstan is analyzed with regard to recognizing the commission of sexual offences against minors by this specific category of persons as an aggravating circumstance. Drawing on examples from judicial practice, the author proposes a broader incorporation of crimes committed by caregivers, educators, and coaches as aggravating qualifying elements in the relevant provisions of the Special Part of the Criminal Code.